Comparison of the Diagnostic Value of Presepsin and Procalcitonin as Markers of Bacterial Sepsis - Fadrian, Fadrian; Ahmad, Armen; Sadeli, Rezki Pratama; Putri, Vidola Yasena; Agustian, Dede Rahman (Institute of Topical Disease Universitas Airlangga, 2026)
Sepsis is a severe condition caused by an improper immune response during infections. Early diagnosis is challenging due to the low specificity and effectiveness of current diagnostic tools. Procalcitonin is a biomarker with both advantages and limitations. Presepsin has emerged as a potential alternative, offering cost-effectiveness, fewer confounding factors, and a quicker response. This study evaluates the diagnostic capabilities of presepsin and procalcitonin in bacterial sepsis. The study involved patients with sepsis who were treated in the Internal Medicine Department at M. Djamil Hospital, Padang, Indonesia. All participants were adults over 18, excluding those with conditions that could affect the biomarkers. A total of 63 patients were assessed. The mean presepsin level in bacterial sepsis was 205.91 pg/mL (±162.65 SD), while procalcitonin averaged 62.83 ng/mL (±80.48 SD). Blood cultures revealed bacterial infections in 18 patients (28.60%). Among them, eight had Gram-positive (44.40%) and ten had Gram-negative bacteria (55.60%). Presepsin demonstrated variable accuracy in identifying bacterial sepsis and bacteremia. The Area Under the Curve (AUC) for bacterial sepsis was 0.60 (95% CI 0.44-0.75), for Gram-positive bacteremia it was 0.63 (95% CI 0.35-0.90), and for Gram-negative bacteremia it was 0.37 (95% CI 0.10-0.65). In contrast, procalcitonin showed an AUC of 0.51 (95% CI 0.35-0.67) for bacterial sepsis, 0.22 (95% CI 0.01-0.46) for Gram-positive bacteremia, and 0.78 (95% CI 0.54-1.00) for Gram-negative bacteremia. Presepsin has a higher diagnostic value than procalcitonin in detecting bacterial sepsis. Procalcitonin has the highest AUC value in all categories for detecting Gram-negative bacteremia.